Multivariate Statistical Process Control untuk Mendeteksi Kerusakan Bearing - Hani Nurhapilah; Sutawanir Darwis (Bandung Conference Series: Statistics, 2023)
Abstract. Multivariate Statistical Process Control is intended to see the stability of a production process so that it becomes effective. This method was developed to detect bearing damage through the T2 Hotelling control chart. Out-of-control is used as a tool to detect bearing condition. The machine is a unit of various interrelated components, resulting in a series of movements. Bearings are important machine components, supporting the shaft to rotate without experiencing excessive friction. Bearing damage detection is important to ensure optimal performance in an industry. The data used is secondary data from the results of bearing vibration experimental tests from the FEMTO-ST Institute. The vibration data used consists of seven bearings with various conditions, each of which consists of two directions, namely horizontal and vertical. Then, the variance features and RMS bearing1_2 and bearing1_4 are taken for data processing. Furthermore, the data is divided into two phases, namely phase-I which is assumed to be the bearing under normal conditions and phase-II which is assumed to be the bearing to be tested. After that, the calculation of the upper control limit (UCL) is carried out in phase-I, and is used in phase-II to detect bearing conditions. The results of tests carried out in phase-II show that there are points that are out-of-control so that it can be said that there are abnormalities in the bearings which may indicate that there are bearings that are abnormal but not necessarily damaged. Abstrak. Multivariate Statistical Process Control diperuntukkan untuk melihat stabilitas proses dari suatu produksi agar menjadi efektif. Metode ini dikembangkan untuk mendeteksi kerusakan bearing melalui diagram kendali T2 Hotelling. Out-of-control digunakan sebagai alat untuk mendeteksi kondisi bearing. Mesin merupakan kesatuan dari berbagai komponen yang saling berkaitan, sehingga menghasilkan suatu rangkaian gerakan. Bearing merupakan komponen mesin yang penting, menumpu agar poros dapat berputar tanpa mengalami gesekan yang berlebihan. Deteksi kerusakan bearing penting dilakukan untuk menjamin performa optimal sebuah industri. Data yang digunakan adalah data sekunder hasil uji eksperimen vibrasi bearing dari FEMTO- ST Institute. Data vibrasi yang digunakan terdiri dari tujuh bearing berbagai kondisi yang masing-masingnya terdiri dari dua arah yaitu horizontal dan vertikal. Kemudian, diambil fitur variansi dan RMS bearing1_2 dan bearing1_4 untuk pengolahan data. Selanjutnya, data tersebut dibagi menjadi dua fase yaitu fase-I yang diasumsikan sebagai bearing kondisi normal dan fase-II diasumsikan sebagai bearing yang akan diuji. Setelah itu, dilakukan perhitungan batas kendali atas (BKA) pada fase-I, dan digunakan pada fase-II untuk mendeteksi kondisi bearing. Hasil pengujian yang dilakukan pada fase-II menunjukkan bahwa terdapat titik-titik yang berada di luar batas kendali (out-of-control) sehingga dapat dikatakan bahwa terdapat ketidaknormalan pada bearing yang mungkin berindikasi terdapat bearing yang tidak normal namun belum tentu rusak.